Blockchain in the courtroom: exploring its evidentiary significance and procedural implications in U.S. judicial processes - Wang, Xukang; Wu, Ying Cheng; Ma, Zhe (Frontiers in Blockchain, 2024)
Blockchain technology's inherent attributes of immutability and security present a transformative potential for evidence law. As several U.S. states have undertaken legislative measures to facilitate the admissibility of blockchain evidence in legal proceedings, this paper explores the evidentiary significance of blockchain records and the procedural implications of integrating this technology into the U.S. judicial system. It examines the Federal Rules of Evidence and their 2017 revision introducing electronic data self-certification, while also analyzing state-level legislation and case law to identify key issues and precedents related to the admissibility and authentication of digital evidence. The paper investigates the fundamental elements of blockchain technology, its legal implications, and the challenges posed by its technical intricacies. It also explores the classification of blockchain evidence in relation to hearsay rules and proposes a comprehensive framework that combines technological and legal perspectives to ensure the consistent integration of blockchain evidence within judicial processes while preserving procedural justice.